Pengawasan Pendistribusian Gas LPG 3 Kg Bersubsidi di Kota Padang - Triola Ramadhan; Roza Liesmana; Roni Ekha Putera (Universitas Lambung Mangkurat, 2019)
This research purpose for describes how Liquifed Petroleum Gas 3 kg distribution controlling in Padang City based from Human Resources and Enery Ministry Regulation No. 26 Tahun 2009 about Liquifed Petroleum Gas 3 kg distribution. Liquifed Petroleum Gas 3 kg is fuel which is having speciality because specific condition like a user/using, packaging, volume and/or the price which have to giving the subsidy. The Liquifed Petroleum Gas 3 kg distribution controlling in Padang City doing by Liquifed Petroleum Gas 3 kg distribution Controlling and Founding Team based on Document Desicion of Region Secretary Padang City No 800.IV.2294.17/Dg 2017. This research using T. Hani Handoko teory about Controlling Phases. This research using qualitative descriptive approach, Data was collected by interview and documentation. The test validity of data found using source triangulation techiques. The result of this research declaire that controlling of distribution Liquifed Petroleum gas 3 kg in Padang City have not effective, it can be found the distribution facilities not having Commercial Business Licence, distribution facilites that sell above the highest retail prices, distribution facilities that do not submit reports on the realization of distribution, implementation of controlling by monitoring team that does not go according to the schedule and initial plan of controlling.